PEMETAAN AIR TANAH DI KABUPATEN JENEPONTO DENGAN METODE GEOLISTRIK - As?ari, As?ari (Sainstek : Jurnal Sains dan Teknologi, 2011)
Data prossesing of groundwater estimate research at Kabupaten Jeneponto, Provinsi Sulawesi Selatan had been done. The research use geoelectric method and Schlumberger configuration. The result of 2-D inversion IP2WIN software show that this method can use for groundwater estimation. We had information of area where there had groundwater potention. Research area divided to 6 path, we know locate and depth information of groundwater from each path, on path 1: Desa Bontorappo and Desa Arungkeke have lower groundwater at 5-15 meter depth and deep groundwater at 45-50 meter depht. Path 2: Desa Balangloe Tarowang and Desa Arungkeke have lower groundwater at 1-15 meter depth and deep groundwater at 20-55 meter depht. Path  3: Kelurahan Benteng have groundwater at 0-100 meter depht. Path 4: Desa Bangkala have groundwater at 30-50 meter depht. Path 5: Desa Torokassi have groundwater at 20-55 meter depht.Key words: groundwater, geoelectric method, Schlumberger configuration